2018
DOI: 10.1093/jee/toy025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Resistance to Cephus cinctus (Hymenoptera: Cephidae) in Barley Germplasm

Abstract: Most barley cultivars have some degree of resistance to the wheat stem sawfly (WSS), Cephus cinctus Norton (Hymenoptera: Cephidae). Damage caused by WSS is currently observed in fields of barley grown in the Northern Great Plains, but the impact of WSS damage among cultivars due to genetic differences within the barley germplasm is not known. Specifically, little is known about the mechanisms underlying WSS resistance in barley. We characterized WSS resistance in a subset of the spring barley CAP (Coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…By consuming conspecific larvae, H. axyridis avoids the potential negative effect of plant toxins [53]. Several previous reports [4,54] and the current study have indicated that a large proportion of C. cinctus neonate mortality indicates that either the host stem tissues contain antibiotic toxins, or possibly the tissues lack some essential nutrients required for neonate growth and development (categorized as plant defense: Table 2, Fig 2). But by consuming conspecific larvae and eggs, first, each cannibal avoids both tissue toxins or diet deficiency and acquires additional nutrient resources.…”
Section: Plos Onementioning
confidence: 52%
See 2 more Smart Citations
“…By consuming conspecific larvae, H. axyridis avoids the potential negative effect of plant toxins [53]. Several previous reports [4,54] and the current study have indicated that a large proportion of C. cinctus neonate mortality indicates that either the host stem tissues contain antibiotic toxins, or possibly the tissues lack some essential nutrients required for neonate growth and development (categorized as plant defense: Table 2, Fig 2). But by consuming conspecific larvae and eggs, first, each cannibal avoids both tissue toxins or diet deficiency and acquires additional nutrient resources.…”
Section: Plos Onementioning
confidence: 52%
“…Wheat stem sawfly, Cephus cinctus Norton (Hymenoptera: Cephidae), successfully adapted from its ancestral wild grass hosts to domesticated spring and winter wheat cultivars [1]. In addition, this species is not only widening its range southward to Colorado and Kansas [2], but it also is increasing infestation and larval survival in barley in Montana [3,4]. To mitigate economic loss, an integrated pest management (IPM) approach has been recommended for wheat across the northern Great Plains [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual economic loss caused by Cephus cinctus damage to wheat is estimated to be $100–350 million in the USA and Canada ( Beres et al, 2011 ). In addition, WSS also damages barley ( Hordeum vulgare L.) and rye ( Secale cereal L.) ( Wallace & McNeal, 1966 ; Beres et al, 2011 ; Varella et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The wheat stem sawfly, Cephus cinctus Norton, is a major pest of wheat in western North America with a southward expanding geographic range likely driven by localized adaptation to cultivated crops from surrounding wildlands (Beres et al 2011;Lesieur et al 2016;Adhikari et al 2018;Varella et al 2018). It is a native species that also uses many other grass hosts and hence plays an important role in the ecology of grasslands (Cockrell et al 2017).…”
Section: Introductionmentioning
confidence: 99%